Arsenic, cadmium, and lead contents of rice imported into Qatar-impact on intake. Issue 1 (21st November 2019) - Elobeid, Tahra; Ganji, Vijay; Moustafa, Khloud; Mohammed, Fatima; El-Ouzi, Loujain; Attieh, Grace
Abstract : Purpose: The purpose of this paper is to determine arsenic, cadmium and lead contents of rice imports and to estimate their impact on these heavy metal intakes in Qatar. Design/methodology/approach: In total, 30 rice samples imported from various countries (Vietnam, Thailand, India, Pakistan, the USA, Australia, the UK and Lebanon) were analyzed for arsenic, cadmium and lead contents with plasma optical spectrometer. These heavy metal intakes from rice were estimated for Qatar population based on the per capita consumption of rice as per 2018 rice consumption data. Findings: In all rice samples, mean concentrations of arsenic, cadmium and lead were 1.11 mg/kg, 19.7  µ g/kg and 131.3  µ g/kg, respectively. Average arsenic, cadmium and lead contents were the highest in rice imported from Thailand (1.25 mg/kg), Vietnam (30  µ g/kg) and India (178.3  µ g/kg), respectively. Estimated arsenic, cadmium and lead intakes through rice consumption by Qatari population were 225.7, 4 and 26.7 µg/day, respectively. Originality/value: In all rice imports, arsenic content is approximately 5.5 times higher than the maximum allowable concentration (MAC), whereas the cadmium and lead levels are within the MAC. Because these heavy metals are linked to health, all Middle Eastern countries that import rice from Thailand, Vietnam and India should monitor the metal contents in their food supply on a regular basis.